Design of Banana Pringles Shaping Machine for Small Industry - Muhd Nor, Nik Hisyamudin; Asnahpon, Misha Nabila (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Banana is a common food that has been consume by the people especially Malaysia. The aims of the study are to design a banana pringles shaping machine especially for small and medium enterprise (SME). The machine will help in production of a new snack and reduce the manpower in order to produce the banana pringles. The step on design a machine that suit the SME specification need a lot of phase like planning, concept generation, conceptual design, embodiment design phase and details design. The mechanism that be used on the machine is same like stamping machine and moulding machine but it more convenient, small and less cost. Compared to manual stamping or moulding, the machine can produce more pieces.